A quantitative determination of fluorochloridone in rat plasma by UPLC‐MS/MS method: application to a pharmacokinetic study. (19th January 2016) - Liu, Shihong; Shi, Jingmin; Fan, Junpei; Sun, Jie; Zhang, Suhui; Hu, Yue; Wei, Li; Wu, Chunhua; Chang, Xiuli; Tang, Liming; Zhou, Zhijun
Abstract: A precise, high‐throughput and sensitive ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) method has been developed for the determination of fluorochloridone (FLC) in rat plasma. The extraction of analytes from plasma samples was carried out by protein precipitation procedure using acetonitrile prior to UPLC‐MS/MS analysis. Verapamil was proved as a proper internal standard (IS) among many candidates. The chromatographic separation based on UPLC was well optimized. Multiple reaction monitoring in positive electrospray ionization was used with the optimized MS transitions at: m / z 312.0 → 292.0 for FLC and m / z 456.4 → 165.2 for IS. This method was well validated with good linear response ( r 2 > 0.998) observed over the investigated range of 3–3000 ng/mL and with satisfactory stability. This method was also characterized with adequate intra‐ and inter‐day precision and accuracy (within 12%) in the quality control samples, and with high selectivity and less matrix effect observed. Total running time was only 1.5 min. This method has been successfully applied to a pilot FLC pharmacokinetic study after oral administration. Copyright © 2016 John Wiley & Sons, Ltd.